1-year results of treatment with rituximab in polymyalgia rheumatica: an extension study of a randomised double-blind placebo-controlled trial. (April 2023) - Bolhuis, Thomas E; Marsman, Diane E; den Broeder, Alfons A; den Broeder, Nathan; van der Maas, Aatke
Summary: Background: Rituximab was effective for patients with polymyalgia rheumatica in the 21-week BRIDGE-PMR randomised controlled trial. Here, we aimed to assess rates of glucocorticoid-free remission up to 1 year after infusion in an extension of this trial. Methods: BRIDGE-PMR was a randomised controlled proof-of-concept trial that enrolled participants with polymyalgia rheumatica according to 2012 European League Against Rheumatism–American College of Rheumatology classification criteria at the Sint Maartenskliniek, Nijmegen, Netherlands. Patients were randomly allocated in a 1:1 ratio to receive one intravenous dose of 1000 mg rituximab or placebo, with identical pre-medication and accelerated glucocorticoid tapering over 17 weeks. After the 21-week study, patients were followed in a double-blind extension until 1 year after infusion during which standard-of-care treatment was provided. The primary outcome after 52 weeks was between-group difference in glucocorticoid-free remission (ie, polymyalgia rheumatica activity score [PMR-AS] <10), assessed in all randomly allocated participants, with data imputed using a predictive mean matching model (provided data were missing at random). A sensitivity analysis restricted to patients with complete data (complete case analysis) was also done. This trial is registered with EudraCT (2018-002641-11) and the Dutch trial database (NL7414). Findings: Between Dec 18, 2019 and June 8, 2021, 47 patients enrolled in the BRIDGE-PMR were followed up in this extension study (23 [11 women and 12 men] allocated rituximab and 24 [13 women and 11 men] allocated placebo), of who 38 had recently diagnosed polymyalgia rheumatica and nine had relapsing polymyalgia rheumatica. Mean (SD) age was 64 (10) years in the rituximab group and 66 (9) years in the placebo group. All participants were White. Missing data were imputed for six participants (four rituximab, two placebo); because the data were probably missing at random, a complete case analysis was added as sensitivity analyses. In the imputed analysis, the between-group absolute difference reached statistical significance (12 [52%] of 23 in the rituximab group in glucocorticoid-free remission vs five [21%] of 24 participants in the placebo group; absolute difference 31% [95% CI 5 to 57], RR 2·5 [1·0 to 6·0]; p=0·04). In the complete case analysis, nine (47%) of 19 patients in the rituximab group were in glucocorticoid-free remission 1 year after infusion compared with five (23%) of 22 in the placebo group (absolute difference 25% [95% CI –4 to 53], relative risk (RR) 2·1 [95% CI 0·8 to 5·2]; p=0·12). Eight (33%) patients in the placebo group and six (26%) in the rituximab group had adverse events. Interpretation: After a single dose of rituximab (1000 mg), the proportion of patients with polymyalgia rheumatica in glucocorticoid-free remission remained stable at 1 year after infusion, and a glucocorticoid sparing effect was evident. A larger trial including possibility for retreatment is warranted to confirm these results. Funding: Sint Maartenskliniek.